El amante diario: carta de Darío a Francisca - Soltero Sánchez, Evangelina (Anales de Literatura Hispanoamericana, 2008)
After the finding of new documents of Rubén Darío in the Rubén Darío Archive, this is the presentation of one of the personal letters that the poet wrote to Francisca Sánchez.